2020
DOI: 10.1080/17453674.2020.1793548
|View full text |Cite
|
Sign up to set email alerts
|

Low arthroplasty survival after treatment for proximal humerus fracture sequelae: 3,245 shoulder replacements from the Nordic Arthroplasty Register Association

Abstract: Background and purpose Proximal humerus fractures (PHF) may result in sequelae indicating arthroplasty. We report cumulative survival rates and reasons for revision after arthroplasty for proximal humerus fracture sequelae (PHFS). Patients and methods Data were derived from the Nordic Arthroplasty Register Association. The Kaplan– Meier method was used to illustrate survival rates. A scaled Schoenfeld residual plot was used to report the risk of revision for men relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…While registries are inadequate for identifying asymptomatic colonized patients, they are excellent tools for collecting large datasets of less frequently performed surgeries. One example is a recent analysis of more than 3000 shoulder replacements from the Nordic Arthroplasty Register Association, which raised concerns over lower-than-previously-reported arthroplasty survival among men undergoing shoulder arthroplasty due to proximal humerus fracture sequelae [9]. Registries should include some additional information on how the diagnosis of shoulder PJI was determined in the first place.…”
Section: How Do We Get There?mentioning
confidence: 99%
“…While registries are inadequate for identifying asymptomatic colonized patients, they are excellent tools for collecting large datasets of less frequently performed surgeries. One example is a recent analysis of more than 3000 shoulder replacements from the Nordic Arthroplasty Register Association, which raised concerns over lower-than-previously-reported arthroplasty survival among men undergoing shoulder arthroplasty due to proximal humerus fracture sequelae [9]. Registries should include some additional information on how the diagnosis of shoulder PJI was determined in the first place.…”
Section: How Do We Get There?mentioning
confidence: 99%
“…Importantly, with the increasing performance of shoulder arthroplasty procedures, also the risk of complications such as periprosthetic joint infection is heightened. A few studies reported revision rates based on large registry data such as the Nordic Arthroplasty Register Association [14][15][16], the Swedish Fracture Register [17] and the Australian Orthopaedic Association National Joint Replacement Registry [18]. However, substantial heterogeneity among studies reporting reoperation rates was noted [19].…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, several treatment options such as humeral osteotomy, hemiarthroplasty (HA), anatomical total shoulder arthroplasty (TSA) or reverse shoulder arthroplasty (RSA) have been suggested [ 2 , 3 , 5 , 6 ]. However, the complication rates are reported to be as high as 45% and the long-term survival rates are reported to be worse [ 1 , 7 ]. For TSA recurrent instability and glenoid loosening have been described, whereas the main problem for RSA is reported to be the fixation of the glenoid component [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%